Courts as organizations : governance and legitimacy - Guimarães, Tomás Aquino (2020)
The interdependence between governance and legitimacy of the courts is a subject that has not been much studied by scholars, especially those from the fields of public administration and organizational studies. Taking into account the importance of these topics for the functioning of these organizations, the purpose of this essay is twofold: to enrich the debate on the contribution of good governance to the legitimacy of courts, and to encourage researchers to address these themes in greater depth. To this end, the main literature on governance and legitimacy of courts is analyzed. Theoretical approaches contribute to the discussion of the functioning of courts, which are highly institutionalized organizations that depend heavily on a presumption of legitimacy. Ensuring this legitimacy has been one of the challenges for these organizations, which are required to adopt governance models that contribute to better management and performance. We argue that there are managerial and substantive implications for society, since the governance and legitimacy of courts can affect the system of justice. We put forward some propositions on the influence of judicial governance on the legitimacy of the justice system and on the perception of legitimacy of the courts. These propositions provide insights for a research agenda on these issues.